Covalency, hybridization and valence state effects in nano- and micro-sized ZnFe2O4. Issue 15 (22nd March 2016) - Singh, Jitendra Pal; Kim, So Hee; Won, Sung Ok; Lim, Weon Cheol; Lee, Ik-Jae; Chae, Keun Hwa
Abstract : In the present work, Fe valence state, covalency effects, and metal–oxygen hybridization are discussed for ZnFe2 O4 using X-ray absorption spectroscopy. Abstract : In the present work, Fe valence state, covalency effects, and metal–oxygen hybridization are discussed for ZnFe2 O4 using X-ray absorption spectroscopy. A few sets of nano-sized and micro-sized zinc ferrite were synthesized using the nitrate method. Nanoparticles of ZnFe2 O4 were synthesized by heating precursor at 300, 400, 500, 800, 1000, and 1200 °C for 1 h. To synthesize micro-sized ZnFe2 O4, the obtained nanoparticles were annealed at 1200 °C for 12 h (bulk treatment). X-ray diffraction shows the presence of cubic spinel phase in nano-sized as well as micro-sized ZnFe2 O4 . Scanning electron microscopy measurements show that particle size ranges are 40–80 nm and 1–2 μm for nano-sized and micro-sized ZnFe2 O4, respectively. Fe L-edge spectra of these materials envisage the presence of spectral features corresponding to t 2g and e g symmetry states created due to Fe(2p3/2 )-Fe(3d) and Fe(2p1/2 )-Fe(3d) in octahedral crystal field. This reflects the presence of Fe 3+ states in nano-sized and micro-sized ZnFe2 O4 . e g states dominate in micro-sized ZnFe2 O4 . O K-edge spectra for these materials can be distinguished by pre-edge and post-edge regions. Pre-edge and post-edge regions are associated with O(2p)–Fe(3d) and O(2p)–Fe(4s, 4p) hybridized states. The extent of hybridization estimated from the intensity ratio of O(2p)–Fe(3d) and O(2p)–Fe(4s, 4p) hybridized states is higher in nano-sized ZnFe2 O4 .